PROBLEMATIKA OTONOMI DAERAH DALAM PERSPEKTIF NEGARA KESATUAN: ANALISIS HUBUNGAN PEMERINTAH PUSAT DAN DAERAH PASCA REFORMASI - Emelianus Jimmy Ell; Bernardus Horokubun; George Frans Wanma (Fakultas Hukum, Universitas Caritas Indonesia, 2026)
Regional autonomy was a key agenda of the 1998 Reform movement, aiming to establish a government that is more democratic, effective, and responsive to the needs of the community. Over time, the implementation of regional autonomy has evolved beyond the mere division of authority between central and regional governments; it now faces new challenges arising from the digital transformation of governance. This study aims to analyze the evolution of regional autonomy and decentralization in the post-Reform era, the dynamics of the relationship between central and regional governments within the framework of a unitary state, and the challenges and effectiveness of local governance in the digital age. The study employs a normative legal research method, utilizing statutory, conceptual, and analytical approaches. Legal materials were gathered from legislation, books, scholarly journals, and other literature relevant to the research theme. The findings indicate that the implementation of regional autonomy has yielded positive outcomes, including increased public participation, the growth of local democracy, and the emergence of public service innovations. However, decentralization efforts still face various obstacles, such as disparities in regional capacity, fiscal dependence on the central government, and a trend toward the recentralization of authority in certain strategic sectors. In the digital era, the effectiveness of local governance is heavily influenced by the readiness of technological infrastructure, the quality of the civil service workforce, regional fiscal capacity, and the synergy between central and regional governments in building an integrated digital governance system. Therefore, strengthening regional capacity and developing a model of